Eccentric training for prevention of hamstring injuries may depend on intervention compliance: a systematic review and meta-analysis. Issue 6 (16th September 2014) - Goode, Adam P; Reiman, Michael P; Harris, Lloyd; DeLisa, Lucia; Kauffman, Aaron; Beltramo, David; Poole, Charles; Ledbetter, Leila; Taylor, Andrea B
Abstract : Background: Hamstring injury is a prevalent muscle injury in sports. Inconclusive evidence exists for eccentric hamstring strengthening to prevent hamstring injuries. One reason for this discrepancy may be the influence intervention non-compliance has on individual study estimates, and therefore pooled estimates. Objective: This systematic review aims to determine the effect of eccentric hamstring strengthening on the risk of hamstring injury and quantitatively explores the impact of intervention non-compliance on the precision, heterogeneity and strength of pooled estimates. Methods: A computer-assisted literature search of Medline, CINAHL, Cochrane, EMBASE, AMED, SportDiscus and PEDro databases was conducted with keywords related to eccentric strengthening and hamstring injury. The search was conducted from the end of a previous comprehensive review forward (1 December 2008 to 31 December 2013). Random-effects models were used for both main effects and a sensitivity analysis. Pooled estimate precision was measured with a confidence limit ratio (confidence limit ratio (CLR); upper limit divided by the lower limit) and heterogeneity was assessed with I 2, Cochrane's-Q and τ 2 . A protocol was not registered for this review. Results: Four out of 349 studies met the inclusion criteria. In main effects analysis, eccentric hamstring training did not reduce the risk of hamstring injury (risk ratio [RR]=0.59 ((95% CI 0.24 to 1.44)). This estimate was imprecise (CLR=6.0) with significant heterogeneity (p value 0.02, 69.6% variation and t 2 =0.57). Subjects compliant with eccentric strengthening had a significant (RR=0.35 ((95% CI 0.23 to 0.55)) reduction in hamstring injuries. This estimate was precise (CLR=2.4) and homogenous (p value=0.38, 2.8% variation and t 2 =0.007). Conclusions: The null-biased effect in using intent-to-treat methods from intervention non-compliance has a substantial impact on the precision, heterogeneity and the direction and strength of pooled estimates. Eccentric strengthening, with good compliance, appears to be successful in prevention of hamstring injury.